HUBUNGAN ANTARA BEBAN KERJA MENTAL DENGAN STRES KERJA PADA MASINIS UPT CREW KERETA API BLITAR DAERAH OPERASIONAL VII MADIUN PT. KERETA API INDONESIA (PERSERO) - Kiki Astrea Trisminingsih (UNUSA Press, 2019)
Machinist is an example of work that uses both mental and physical aspect. The potential of machinist experiencing work stress also depends on the workload borne. The purpose of this study was to analyze the relationships of the mental workload with work stress. The population of this study was all the UPT Crew VII Operational Area Madiun, PT. Kereta Api Indonesia (Persero), which is as many as 24 machinists. The number of samples taken from the entire population. The dependent variable in this study was a mental workload and the independent variable was work stress. Based on the research, it can be concluded that the majority of machinists (58.3%) have a heavy mental workload, and 75% of machinists experience high levels of work stress. From the statistical test obtained the value of the contingency coefficient is 0.683, so it can be concluded that there is a strong relationship between mental workload and work stress on machinists UPT Crew Blitar Railway VII Operational Area Madiun PT. Kereta Api Indonesia (Persero).